Estudo comparativo da legislação ambiental no licenciamento de suinocultura nos estados do Rio Grande do Sul e de Santa Catarina - Motta, Lori Inês Rossi da (2024)
This dissertation addresses the environmental legislation applicable in the pig farming licensing in Rio Grande do Sul and, Santa Catarina States, aiming to compare their guidelines and identify similarities and differences between them. The research aims to analyze the main characteristics of environmental regulations in each State, highlighting their approaches to promoting sustainable pig farming and minimizing the environmental impacts associated with this activity The methodology involved a detailed review of relevant State laws, as well as resolutions of environmental councils, focusing on the comparative analysis of provisions regarding pig farming licensing. The results regarding the monitoring of waste application areas and environmental programs reveal that although both States share the common objective of protecting the environment and promoting the sustainable development of the agricultural sector in swine farming, the regulations may vary in specific details, reflecting the different environmental and legislative realities of each region, their legislation presents different approaches, with Santa Catarina placing greater emphasis on sustainability and adopting more rigorous measures for environmental control compared to Rio Grande do Sul. Understanding these differences and similarities is essential for guiding effective public policies and promoting environmentally responsible agricultural practices.